Congenital and oral transmission of American trypanosomiasis: an overview of physiopathogenic aspects (2013)
Chagas disease or American trypanosomiasis is a pathology affecting about 8–11 million people in Mexico, Central America, and South America, more than 300 000 persons in the United States as well as an indeterminate number of people in other non-endemic countries such as USA, Spain, Canada and Switzerland. The aetiological agent is Trypanosoma cruzi, a protozoan transmitted by multiple routes; among them, congenital route emerges as one of the most important mechanisms of spreading Chagas disease worldwide even in non-endemic countries and the oral route as the responsible of multiple outbreaks of acute Chagas disease in regions where the vectorial route has been interrupted. The aim of this review is to illustrate the recent research and advances in host-pathogen interaction making a model of how the virulence factors of the parasite would interact with the physiology and immune system components of the placental barrier and gastrointestinal tract in order to establish a response against T. cruzi infection. This review also presents the epidemiological, clinical and diagnostic features of congenital and oral Chagas disease in order to update the reader about the emerging scenarios of Chagas disease transmission.